EARNINGS ANNOUNCEMENTS AND COMPETING INFORMATION: THE INDONESIAN EVIDENCE - Sulistiawan, Dedhy; Hartono, Jogiyanto; Tandelilin, Eduardus; Supriyadi, Supriyadi (Journal of Indonesian Economy and Business, 2014)
The main purpose of this study is to provide empirical evidence of the relationship betweeninvestorsâ responses to two events, which are, (1) earnings anouncements, and (2) technicalanalysis signals, as competing information. This study is motivated by Francis, et al. (2002),whose study used stock analystâs recommendations as competing information in the U.S stockmarket. To extend that idea, this study uses technical analysis signals as competing informationin the Indonesian stock market. Using Indonesian data from 2007-2012, this study shows thatthere are price reactions on the day of a technical analysis signalâs release, which is prior toearnings announcements. It means that investors react to the emergence of competinginformation. Reactions on earnings announcements also produce a negative relationship withthe reaction to a technical analysis signal before an earnings announcement. This study givesevidence about the importance of technical analysis as competing information to earningsannouncements.Keywords: competing information, earnings announcements, technical analysis, price reaction